PENGARUH KUALITAS PELAYANAN DAN KEPERCAYAAN MEREK TERHADAP KEPUASAN NASABAH (STUDI PADA NASABAH PRODUK PENGHIMPUN DANA BANK BNI SYARIAH KANTOR CABANG PEKANBARU) - Rury Almadea; Endang Sutrisna (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This study aims to determine the effect of service quality and brand trust on customer satisfaction in customers of Bank BNI Syariah funds product Pekanbaru Branch Office partially and simultaneously. This study uses questionnaires as a means of collecting data distributed to 100 customers of funds collecting products Bank BNI Syariah Pekanbaru Branch Office. Data from the questionnaire was further processed using descriptive analysis and statistical analysis using SPSS 17.0 by performing validity test, reliability test, simple linear regression analysis, multiple linear analysis, coefficient of determination analysis, and hypothesis test consisting of t test (partial) and F test (Simultaneous).The results showed that the results of the first hypothesis testing is service quality to customer satisfaction showed t count (5,436) > t table (1,984), it means service quality significantly influence customer satisfaction. The result of second hypothesis testing is brand trust to customer satisfaction show t count (7,143) > t table (1,984), it means brand trust have significant effect to customer satisfaction. The result of the third hypothesis testing, namely service quality and brand trust on customer satisfaction shows F count (26,610) > F table (3.09), it means service quality and brand trust have significant effect to customer satisfaction.Keywords: Service Quality, Brand Trust, Customer Satisfaction